Nanocellulose: From Fundamentals to Advanced Applications - Trache, Djalal; Tarchoun, Ahmed Fouzi; Derradji, Mehdi; Hamidon, Tuan Sherwyn; Masruchin, Nanang; Brosse, Nicolas; Hussin, M. Hazwan (Frontiers in Chemistry, 2020)
Over the past few years, nanocellulose (NC), cellulose in the form of nanostructures, has been proved to be one of the most prominent green materials of modern times. NC materials have gained growing interests owing to their attractive and excellent characteristics such as abundance, high aspect ratio, better mechanical properties, renewability, and biocompatibility. The abundant hydroxyl functional groups allow a wide range of functionalizations via chemical reactions, leading to developing various materials with tunable features. In this review, recent advances in the preparation, modification and emerging application of nanocellulose, especially cellulose nanocrystals (CNCs), are described and discussed based on the analysis of the latest investigations (particularly for the reports of the past three years). We start with a concise background of cellulose, its structural organization as well as the nomenclature of cellulose nanomaterials for beginners in this ﬁeld. Then, different experimental procedures for the production of nanocelluloses, their properties, and functionalization approaches were elaborated. Furthermore, a number of recent and emerging uses of nanocellulose in nanocomposites, Pickering emulsifiers, wood adhesives, wastewater treatment, as well as in new evolving biomedical applications are presented. Finally, the challenges and opportunities of NC-based emerging materials are discussed.